Hubungan Sedentary Behavior dengan Tekanan Darah Pada Pegawai Bank di Bandung - Sharon Nafthalia; Ni Luh Widani; Sada Rasmada (I Care Jurnal Keperawatan STIKes Panti Rapih, 2020)
Background: In this era of modernization, sedentary behavior (SB) has developed in society. Banker work for ± 8 hours every day. Objective: This research was conducted to determine the relationship of sedentary behavior with blood pressure of bankers in Bandung. Methods: This research is a quantitative study with a cross-sectional method, which was conducted in Febuary – April 2020. The sampling technique in this study was purposive sampling of 70 employees. The Global Physical Activity Questionnaire (GPAQ) is used as a SB measurement tool that has been tested for validity and reliability (r = 0,45 – 0.63). Result: The results of univariate analysis showed that 75.5% of employees behaved in SB. The results of the Wilcoxon test analysis of systolic and diastolic blood pressure showed a significant difference (sig = 0.000). Bivariate analysis with chi – square test (α <0.05) found statistically significant correlation between SB with morning systolic blood pressure (TDS) (p value = 0.005) and diastolic blood pressure (TDD) (p value = 0.003), daytime TDS (p value = 0.002) and afternoon TDD (p value = 0.003), afternoon TDS (p value = 0.005) and afternoon TDS (p value = 0.004). Conclusion: The conclusion of this study is that there is a relationship between sedentary behavior with the three blood pressure measurements. It is expected that employees can compensate by doing moderate or vigorous activity during free time.